Efektivitas pembelajaran matematika melalui whatsapp grup selama wabah covid-19 di kelas V SDN 1 Brujul - Nia Amarthani; Sandra Bayu Kurniawan; Peduk Rintayati (Universitas Sebelas Maret, 2021)
The research purpose to analyze the effectiveness of learning mathematics using whatsapp group in class V SDN 1 Brujul. The research was conducted using qualitative techqniques with a phenomenological approach. This research data collection using observation, interviews and documentation. The validity of the data used was triangulation source and triangulation technique. The data in this study were processed using inductive data processing techniques according to Miles and Huberman. The result of this study resulted in six focus meanings wherw there were implementation of learning, learning facilities, presentation of material, understanding of the material and learning outcomes. The six meanings related to each other, which can be conclude that learning mathematics using whatsapp group in class V SDN 1 Brujul is not effective. This ineffectiveness is due to the ineffective facilities, the lack of material presentation, the lack of guidance from the teacher and the obstacles that arise during the learning process.